PENGGUNAAN MODEL PEMBELAJARAN CONCEPT SENTENCE UNTUK MENINGKATKAN AKTIVITAS SISWA DAN KETERAMPILAN MENULIS KARANGAN NARASI - Anggi Citra Apriliana; Wina Hermawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2020)
This research is motivated by the results of observations which show that the activities and writing skills of narrative essays by Grade IV students of Santaka Elementary School Cimanggung District, Sumedang Regency are still low. This is indicated by the low understanding of students in learning narrative essay writing skills and student activities that are classified as passive during learning. The purpose of this research is to improve the activities and writing skills of students' narrative essays by applying the Concept Sentence learning model. The research method used is PTK with Kemmis and Mc. Taggart. This research consisted of two cycles with 23 students. Based on the results of data analysis, it is known that the increase in student activity is seen from the average pre-cycle learning outcomes reaching 39%, then increasing in the first cycle after using the Concept Sentence model with an average of 70% and the second cycle reaching 83%. This shows an increase in student activity in learning to write narrative essays. The narrative essay writing skills in the initial conditions reached 26%, then increased in the first cycle with an average of 65% and in the second cycle reached 87%. This shows that the students' narrative essay writing skills have increased in each cycle with the application of the Concept Sentence model.